DOI: 10.15368/theses.2008.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Filtration Temperature and Heat Treatment on Composition and Rheological Properties of Whole Milk Ultrafiltration Retentates

Abstract: Effects of Filtration Temperature and Heat Treatment on Composition and Rheological Properties of Whole Milk Ultrafiltration Retentates John William MontellaFor the first part of my thesis, the effects of filtration temperature and heat treatment on the compositional properties of whole milk Ultrafiltration retentate (UF) were studied.Ultrafiltration is primarily run at temperatures in the range of 50-55°C but more and more plants are starting to filter at refrigeration temperatures. In the ultrafiltration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Ozimek et al (1988) observed non-significant difference between the HCT of fresh and a week old samples of UF retentate. Montella (2008) investigated the impact of batch pasteurization (before and after UF treatment) and ultrafiltration temperature (either 10 or 50°C) on compositional and rheological properties (i.e. viscosity, at 10, 40 and 70°C; 500 s -1 shear rate) of 39 UF retentates obtained from whole bovine milk.…”
Section: Introductionmentioning
confidence: 99%
“…Ozimek et al (1988) observed non-significant difference between the HCT of fresh and a week old samples of UF retentate. Montella (2008) investigated the impact of batch pasteurization (before and after UF treatment) and ultrafiltration temperature (either 10 or 50°C) on compositional and rheological properties (i.e. viscosity, at 10, 40 and 70°C; 500 s -1 shear rate) of 39 UF retentates obtained from whole bovine milk.…”
Section: Introductionmentioning
confidence: 99%